POTENSI SERANGGA DI SEKITAR TANAMAN PADI (Oryza sativa L.) PADA AREAL PERSAWAHAN LALETEN KABUPATEN MALAKA - Ludgardis Ledheng; Maria F. S. Seran; Blasius Atini (Politeknik Pertanian Negeri Kupang, 2017)
Rice field ecosystem is artificial ecosystem. Insects as one of the rice field eccosystem components play a pivotal role in the food chain which is as herbivore, predator and detrivore. This research aims to identify insects in the rice field at Laleten Vilagge. Also potential insects, and factors affecting the insects’ activities were investigated. The research was conducted in Malaka Regency, East Nusa Tenggara during March, 2017. The research method was Trap Method using net and lamp. Biological wealth equation was used to assess the potential insects. The results shows that insects in the rice field of Laleten were grouped in three based on their role as predator, herbivore and detrivore. Insects found in the net trap were 8 species, 7 families, and 6 ordos. Insects found in the lamp trap was 1 species, 1 family and 1 ordo. From all the insects, it was identified insect diversity values as followed; 54.26 for predators, 35.12 for herbivore and 30.79 for detrivore. The average of biodiversity value (R) was 120, 17. Key word: Potential insect, rice field, Lateten Village